2021
DOI: 10.3390/nu13030769
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of a 13-Week Pilot Randomised Controlled Trial Testing the Effects of Incremental Doses of Beetroot Juice in Overweight and Obese Older Adults

Abstract: Nitrate-rich food can increase nitric oxide production and improve vascular and brain functions. This study examines the feasibility of a randomised controlled trial (RCT) testing the effects of prolonged consumption of different doses of dietary nitrate (NO3-) in the form of beetroot juice (BJ) in overweight and obese older participants. A single-blind, four-arm parallel pilot RCT was conducted in 62 overweight and obese (30.4 ± 4 kg/m2) older participants (mean ± standard deviation (SD), 66 ± 4 years). Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Other results have been reported elsewhere [ 33 ]. Briefly, a one-way ANOVA revealed that there was a statistically significant increase in the change from baseline in plasma NO 3 − concentration at 13 weeks ( p < 0.001) with increasing beetroot juice consumption.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Other results have been reported elsewhere [ 33 ]. Briefly, a one-way ANOVA revealed that there was a statistically significant increase in the change from baseline in plasma NO 3 − concentration at 13 weeks ( p < 0.001) with increasing beetroot juice consumption.…”
Section: Resultssupporting
confidence: 78%
“…Our participants were asked to maintain their habitual dietary habits, physical activity, and medication throughout the study. Finally, the increase in concentrations of NO 3 − and NO 2 − biomarkers with increasing beetroot juice dose (as reported elsewhere [ 33 ]) provide assurance that the participants were compliant in consuming the beetroot juice supplements.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations